Antecedents of blockchain technology adoption intentions in the supply chain. (18th March 2020) - Sheel, Ashutosh; Nath, Vishnu
Supply chain involves a lot of transactions among the stakeholders. Blockchain technology will make a revolutionary change the way how transactions are being carried out. Blockchain removes all the disadvantages which are related to trust among stakeholders and gives better visibility and transparency. The present study explores factors that affect blockchain technology adoption in the supply chain. The current study is based on the extended unified theory of acceptance and use of technology (UTAUT2) with trust model. Data was collected from 363 supply chain practitioners from India. The results of the present study indicate that behavioural intentions are positively and significantly influenced by performance expectancy, effort expectancy, hedonic motivation, price value, and trust. The study also lists out various aspects for future research regarding the implementation of blockchain in supply chain management.